Agriculture and climate change: Synergies among mitigation, adaptation, and sustainable development - Smith, Pete (International Food Policy Research Institute, 2009)
There is very significant cost-effective greenhouse gas (GHG) mitigation potential in agriculture. The mitigation potential at a range of future carbon prices is similar to the potential in the industry, energy, transport, and forestry sectors. Using economic mitigation potentials from the Intergovernmental Panel on Climate Change’s Fourth Assessment Report (IPCC AR4), the yearly mitigation potential in agriculture is estimated to be worth between US$32 billion and US$420 billion at carbon prices between US$20 and US$100 (t CO2-eq.-1).1 From both a mitigation perspective and an economic perspective, we cannot afford to miss out on this opportunity. But many mitigation options also offer the promise of facilitating adaptation to climate change and contributing to sustainable development more generally. In this brief, synergies between mitigation, adaptation, and sustainable development are described so that multiple policy goals can be identified when considering how to include agriculture in the climate change negotiations in Copenhagen.